ISRAELI EDUCATION MARKET - Awada, Saleh (PUBLISHINGS of Kostanay State Pedagogical Institute, 2016)
In the past 50 years participation in the education system has increased and the upgrading of the occupational structure as a result of industrialization processes has created, inter alia, a demand for a skilled, sophisticated and highly educated labor force). Concurrently, educational qualifications have become important step for employment at the bottom of the occupational hierarchy. As most individuals in post-industrial societies attain secondary education, the proportion of occupations that require post-secondary education has grown, and is projected to continue growing. Although high-level credentials have become more important, there is relatively little research on the transition from higher education to work. This transition is usually conceptualized as labor market consequences of a very crude classification of vocational versus academic tracks in higher (mainly secondary) education. There are little number of researches that have explored labor market consequences using a detailed classification of tertiary education. In this article, we focus on two important aspects of tertiary education: type of given degree and field of study.
Keywords: secondary education; employment; qualified graduate